Use of genome wide expression profiles in analysis of T cell dysfunction in Hepatitis C virus infection - Gupta, P (2014)
During the course of infection with chronic pathogens such as Hepatitis C virus (HCV), Hepatitis B virus (HBV) and HIV, virus-specific CD8+ T cells differentiate into heterogeneous dysfunctional subpopulations. Advances in multi-parameter flow cytometry have allowed these subpopulations to be further classified into classes of exhausted T cells, primarily by their expression of multiple inhibitory receptors. However, the exact phenotype of CD8+ T cells during exhaustion is an area of great interest as many inhibitory receptors are also expressed on functional CD8+ T cells. Discovering novel and specific markers of T cell exhaustion is fundamental in developing strategies to restore CD8+ T cell function in chronic viral infections. Recently, genome wide expression profiles have identified broad molecular phenotypes in exhausted T cells that could not have been discovered by flow cytometry alone. I show how similar genomic approaches identify and further characterise the ectonucleotidase CD39 as a novel marker of CD8+ T cell exhaustion in chronic viral infection. I show that CD39 is highly expressed in HCV and HIV-specific CD8+ T cells and that CD39+ CD8+ T cells are enriched with gene signatures of exhaustion. CD39 is highly co-expressed with multiple inhibitory receptors including PD-1, enzymatically active on CD8+ T cells in HCV infection and positively correlated with viral load in both HCV and HIV. I also demonstrate the discovery of a novel CD39High population of cells in the mouse model of chronic Lymphocytic Choriomenigitis Virus (LCMV) infection, which express the highest degrees of PD-1, LAG3 and 2B4 in the CD39+ fraction. Thus, CD39 is a novel and specific marker of severe CD8+ T cell exhaustion in human and animal models of chronic viral infection.